Carbon dioxide reforming of methane to synthesis gas over Ca and Mg promoted Pt and Ni catalysts supported on γ-Al2O3. - Yee, Choon Hau. (2010)
Different base metals and promoters were investigated for its suitability as catalyst for dry reforming reaction by investigating its catalytic performance, stability and coke formation. Pt, Ni, Ru, Pd, Co, Pt-Ca, Pt-Mg, Ni-Ca and Ni-Mg supported on Al2O3 were synthesized using the wet co-impregnation method. The fresh and spent catalysts were characterized by XRD, TPR and TGA to determine type of species present as well as coke formation. The results revealed that Pt and Ni are the most suitable base metals for the reaction due to its high activity and stability. Reduced NiAl2O4 species improved the dispersion and acted as the active site for the reaction. It has been found that the adding of Ca and Mg promoters to Pt did not have any significant effect as there was already existing strong interaction between the Pt species and the support. Ni-Mg/γ-Al2O3 had reduced coke formation due to the strong interaction between Mg particles and the support. Mg helped to neutralize the strong acidic sites of the alumina support and improve its thermal stability. Ni-Ca/Al2O3 proved to be the promising catalyst for dry reforming reaction as it exhibited a marginal higher activity with reduced amount of coke formation and is highly affordable. The forming of CaO increased the ionic density and favored the adsorption of CO2 on the alumina surface through attraction effects. Possible future studies can be done to investigate the optimal loading for Ca promoters to achieve maximum activity.